2014
DOI: 10.1002/asi.23278
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the information‐seeking behavior of software engineers

Abstract: Information seeking in the workplace can vary substantially from one search to the next due to changes in the context of the search. Modeling these dynamic contextual effects is an important challenge facing the research community because it has the potential to lead to more responsive search systems. With this motivation, a study of software engineers was conducted to understand the role that contextual factors play in shaping their information‐seeking behavior. Research was conducted in the field in a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…The first two phases of the study, which have been published elsewhere, provided evidence of a relationship between task and genre (Freund, 2011;Freund et al, 2005). A third study, reported below, was designed to validate and extend these findings by exploring the relationships between specific tasks and genres.…”
Section: Study One: Software Services Workplacementioning
confidence: 93%
See 2 more Smart Citations
“…The first two phases of the study, which have been published elsewhere, provided evidence of a relationship between task and genre (Freund, 2011;Freund et al, 2005). A third study, reported below, was designed to validate and extend these findings by exploring the relationships between specific tasks and genres.…”
Section: Study One: Software Services Workplacementioning
confidence: 93%
“…In the first, interviews with software engineering consultants revealed that the types of tasks in which they are engaged influence the characteristics of information sought and the search strategies employed. One of the key strategies reported was to seek familiar document genres that were known to have the desired characteristics (Freund, 2011). A follow-up study with the same population (Freund et al, 2005) examined the relationship between tasks and genres in a large, shared document repository.…”
Section: Task-genre Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some studies focusing on information needs and seeking behaviours of diverse communities (e.g., scientists (Niu & Hemminger, 2012;Palmer 1999;Sahu 2013); engineers (Freund 2015); nurses (McKnight 2007;Sundin 2002)). However, very few studies (e.g., Ikoja-Odongo & Ocholla, 2003;Njoku, 2004) focus on information needs and seeking behaviour of fishermen.…”
Section: Problem Statementmentioning
confidence: 99%
“…Plösch et al [7] assessed the most important quality attribute of software documentation via a survey. Related to search of information, Freund [4] explored what contextual factors impact the information seeking behaviour of software engineers. The focus of our work, which is storage and search for documents, is different from the previous studies.…”
Section: Related Workmentioning
confidence: 99%